2021
DOI: 10.1371/journal.pone.0252044
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting prehospital time delay of the injured patients arriving at the Emergency Department of Beni-Suef University Hospital in Egypt: A cross-sectional study

Abstract: Purpose This study aimed to assess the factors affecting the prehospital time delay of the injured patients arriving at the Emergency Department of Beni-Suef University Hospital in Upper Egypt. Materials and methods In this cross-sectional study, the following data were retrieved from the hospital records of 632 injured patients between 1/1/2018 and 31/3/2018: age, sex, residence, means of transportation to the hospital, prehospital time delay, consciousness level on admission, source of injury, and type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…found that there is an increased mortality rate of up to 14.3% in patients with delayed presentation of more than 2 hours to the emergency department in Suez Canal university hospital. 17 Khalil et al ., 18 at Beni-Suef university in Upper Egypt, found that patients over 60 years old and with rural residency were associated with pre-hospital delays of more than 60 minutes, while patients with decreased consciousness levels seem to suffer fewer hospital delays. This is due to the overcrowded streets of large cities, such as Cairo, patients’ awareness of the number of ambulance services, and inadequate training of the paramedic crew.…”
Section: Deficits Of Trauma Care In Egyptmentioning
confidence: 99%
“…found that there is an increased mortality rate of up to 14.3% in patients with delayed presentation of more than 2 hours to the emergency department in Suez Canal university hospital. 17 Khalil et al ., 18 at Beni-Suef university in Upper Egypt, found that patients over 60 years old and with rural residency were associated with pre-hospital delays of more than 60 minutes, while patients with decreased consciousness levels seem to suffer fewer hospital delays. This is due to the overcrowded streets of large cities, such as Cairo, patients’ awareness of the number of ambulance services, and inadequate training of the paramedic crew.…”
Section: Deficits Of Trauma Care In Egyptmentioning
confidence: 99%
“…Although health conditions requiring a rapid response are on the rise,4 EMS is not part of medical care in many low and middle-income countries 5. Because most of these countries lack an EMS, delays in treatment are prevalent, particularly in rural areas 6–11…”
Section: Introductionmentioning
confidence: 99%
“…5 Because most of these countries lack an EMS, delays in treatment are prevalent, particularly in rural areas. 6–11 …”
Section: Introductionmentioning
confidence: 99%